TIPIFICACIÓN MORFOLÓGICA DE CURSOS PRINCIPALES. CUENCA DEL ARROYO EL NEGRO, SISTEMA DE VENTANIA, ARGENTINA - Alicia M. Campo; Verónica Gil; Guadalupe Ybarra Alcaráz; Antonela Volonté (Boletín Geográfico)
Rivers are natural, dynamic and complex systems. Its main function is the transportation of water, sediments and nutrients, conforming areas of great ecological and territorial value. Morphology varies according to the structure and the drainage network. Fluvial systems typification classifies and characterize rivers in order to provide substantial information about every section. Although there are several classifications and characterizations, Rosgen’s combines hydrological, geomorphological and ecological aspects that serves as important indicators towards this study. River classifications are relevant to understanding natural systems and their function, being an instrument of major importance in territorial planning, which provides a significant benefit to environment and society. The area encloses the lower basin of El Negro stream in Sierra de la Ventana, Argentina. Thehomonym village occupies part of the floodplain of the main channel. In recent years, the real estate pressure in these areas led to the opening of new subdivisions for the construction of resorts, changing the stream morphology. The aim of this work is to morphologically characterize and typify a section located in the lower basin of El Negro stream to generate a methodology applicable to other courses in the sector. Before typification, sectioning was implemented following criteria by Ollero Ojeda y otros (2003) and utilizing aerial photographs. The corresponding portion of the lower basin was selected for morphological characterization as the one showing major changes due to being in the urbanized area. The investigation was done based on Thorne’s methodology (1998), and afterwards typified following Rosgen’s criteria (1994). The typification resulted in a A3 stream category based on its morphological characteristics. The methodology allows to comprehend fluvial dynamics and gather data from a sector where scarces or nonexists, in order to generate representative information about hydrogeomorphological conditions that may be taken into account by authorities.